Development of Cognitive and Imaging Biomarkers Predicting Risk of Self-Blaming Bias and Recurrence in Major Depression - Zahn, Roland; The University of Manchester (King’s College London, 2019)
This data-set consists of fully anonymised task-based fMRI using a value-related moral sentiments task which probes emotions related to self-blame such as guilt and blaming others, such as anger, structural 3 dimensional T1 weighted and resting-state fMRI data for remitted MDD and Healthy Control participants taking part in our studies. Data sharing is stipulated by our MRC-approved data management plan. Basic anonymised clinical and demographic descriptors are also available.In addition to the anonymised clinical data, the dataset also includes anonymised results of standard questionnaires, phenomenological psychopathology and neurocognitive tasks probing moral sentiments, emotional memory, action tendencies, and social knowledge which were described in our papers, alongside some unpublished data which can be used after seeking permission from the chief investigator. Data from the following publications are entailed in the dataset which should be cited when using the different aspects of the data:-Gethin J.A., Lythe K.E., Workman C.I., Mayes A., Moll J., Zahn R. Early life stress explains reduced positive memory biases in remitted depression. Eur Psychiatry (2017) 45:59-64: Early life event classification and emotional recognition memory test-Workman C.I., Lythe K.E., McKie S., Moll J., Gethin J.A., Deakin J.F.W., Elliott R., Zahn R. A novel resting-state functional MRI signature of resilience to recurrent depression. Psychological Medicine (2017) 47: 597–607: Resting state fMRI data with prospective clinical follow-up of remitted MDD participants over 14 months-Workman C.I., Lythe K.E., McKie S., Moll J., Gethin J.A., Deakin J.F.W., Elliott R., Zahn R. Subgenual cingulate-amygdala functional disconnection and vulnerability to melancholic depression. Neuropsychopharmacology (2016) https://doi.org/10.1038/npp.2016.8: Resting state fMRI cross-sectional MDD vs Healthy Control comparisons-Lythe K.E., Moll J., Gethin J.A., Workman C.I., Green S., Lambon Ralph

M.A., Deakin J.F., Zahn R. Self-blame-selective hyperconnectivity between anterior temporal and subgenual cortices and prediction of recurrent depressive episodes. JAMA Psychiatry (2015): https://doi.org/10.1001/jamapsychiatry.2015.1813: Prospective fMRI data for prediction of 14 months clinical follow-up in remitted MDD (Karen Lythe Sample)-Zahn R., Lythe K.E., Green S., Gethin J.A., Deakin J.F., Young A.H., Moll J. The role of self-blame and worthlessness in the psychopathology of major depressive disorder. Journal of Affective Disorders (2015) DOI: http://dx.doi.org/10.1016/j.jad.2015.08.001: Psychopathological assessment (AMDP) and moral emotion addendum-Zahn R., Lythe K.E., Gethin J.A., Green S., Deakin J.F., Workman C., Moll J. Negative emotions towards others are diminished in remitted major depression. European Psychiatry (2015) https://doi.org/10.1016/j.eurpsy.2015.02.005: VMST=MST(value-related moral sentiment task)-Green S., Lambon Ralph M., Moll J., Zakrzewski J., Deakin J.F.W., Grafman J., Zahn R. The neural basis of conceptual-emotional integration and its role in major depressive disorder. Social Neuroscience (2013) 8(5): 417-433: CSKD: conceptual social knowledge differentiation task – unpublished additional data included in dataset-Green S., Moll J., Deakin J.F.W., Hulleman J., Zahn R. Proneness to decreased negative emotions in major depressive disorder when blaming others rather than oneself. Psychopathology (2013) 46(1): 34-44: VMST=MST(value-related moral sentiment task)-Green S., Lambon Ralph M., Moll J., Deakin J.F.W., Zahn R. Guilt-selective functional disconnection of anterior temporal and subgenual cortices in major depressive disorder. Archives of General Psychiatry (2012) 69(10): 1014-1021: cross-sectional fMRI (Sophie Green sample)-Duan S., Lawrence A., Valmaggia L., Moll J., Zahn R. The role of blame-related action tendencies in the vulnerability to major depressive disorder. MedRxiv 2020: https://doi.org/10.1101/2020.11.

15.20232058: Action tendencies task (action)-Lythe KE, Gethin JA, Workman CI, Lambon Ralph MA, Deakin JFW, Moll J, et al. Subgenual activation and the finger of blame: individual differences and depression vulnerability. Psychol Med 2020: 1-9: Description of autonomy and sociotropy dimensions of self-blame and its association with fMRI results.
Keywords: Resting fMRI; Structural 3D MRI; Remitted Major Depressive Disorder; self-blame; guilt; anger; disgust; fMRI; moral emotion